Baader-Meinhof and the Novel Narratives of the Nation / Fantasies of the Revolution, 1970–2010 - Preece, J.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2012)
The Baader-Meinhof Group and other violent underground organizations have provided material to many novels by leading German and international writers. This book is the first to examine this rich literary corpus, treating it as a political unconscious which expresses submerged anxieties and moral blind-spots in Europe's most powerful country.
Keywords: Europe, Central—History.; Literature, Modern—20th century; Literature; Fiction; Europe—History.; Literature—History and criticism; History of Germany and Central Europe; Twentieth-Century Literature; Literature, general; Fiction; European History; Literary History